2020
DOI: 10.1177/1049732320925796
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and Concerns of Older Adults With Cognitive Impairment About Their Relationship With Medical Providers: A Call for Therapeutic Alliances

Abstract: We sought to understand the expectations and concerns of older adults with cognitive impairment with regard to their relationship with medical providers. In particular, we observed whether study participants were involved in therapeutic alliances. Medical providers and patients create therapeutic alliances when they agree on the goals of the treatment and share a personal bond. Whereas such alliances have been studied in cancer research, little is known about therapeutic alliances in dementia research. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…Consistent with previous research (Koehn et al, 2016; Portacolone et al, 2020), we further found that participants who felt a lack of rapport or empathy from their health care providers were likely to resist offers of care such as medication or follow-up appointments:[The doctor] said “I can be your neurologist,” and I thought [my wife’s] not gonna come back to see you . .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with previous research (Koehn et al, 2016; Portacolone et al, 2020), we further found that participants who felt a lack of rapport or empathy from their health care providers were likely to resist offers of care such as medication or follow-up appointments:[The doctor] said “I can be your neurologist,” and I thought [my wife’s] not gonna come back to see you . .…”
Section: Resultssupporting
confidence: 86%
“…The interpersonal dimensions of health interactions. Consistent with previous research (Koehn et al, 2016;Portacolone et al, 2020), we further found that participants who felt a lack of rapport or empathy from their health care providers were likely to resist offers of care such as medication or follow-up appointments: When I would ask questions, he would always say things like, "Ask your family doctor." He didn't want to answer anything.…”
Section: Offers and Resistancesupporting
confidence: 85%
“…Although we found a high prevalence of any I/ADL difficulty among the entire analytic sample of older adults living alone with probable dementia/CIND, the true percentages could be higher. Qualitative studies [28][29][30] have found that respondents sometimes understate needs to avoid unwanted relocations. Further, cognitive impairment might reduce respondents' ability to assess their own capacity to perform specific I/ADLs.…”
Section: Difficulty and Help Received With Specific I/adlsmentioning
confidence: 99%
“…Three studies (Karnieli-Miller et al, 2007; Karnieli-Miller, Werner, Neufeld-Kroszynski et al, 2012; Portacolone et al, 2020) used an observational approach to understand more about the interaction of clinicians with the person and carer during disclosure. In a study from Israel, three neurologists with considerable experience of dementia disclosure, felt they made an honest and appropriate disclosure.…”
Section: Resultsmentioning
confidence: 99%